Malpractice in Otology. Issue 4 (26th July 2013) - Blake, Danielle M.; Svider, Peter F.; Carniol, Eric T.; Mauro, Andrew C.; Eloy, Jean Anderson; Jyung, Robert W.
Abstract : Objective: (1) Analyze otologic procedural malpractice litigation in the United States of America. (2) Discuss ways to prevent future malpractice litigation. Study Design and Setting: Case series with record review. Methods: The study is a case series with review of court records pertaining to otologic procedures using the Westlaw legal database. The phrase medical malpractice was searched with terms related to otology and neurotology obtained from the AAO‐HNS website. Results: Of the 47 claims that met inclusion criteria, 63.8% were decided in the physician's favor, 25.5% were decided in the plaintiff's favor (average payment 446, 697), and 10.6% were settled out of court (average payment 372, 607). Cerumen removal was the most common procedure leading to complaint (21.3%) and the most likely procedure to lead to payment (50.0%). Hearing loss was the most common injury claimed among all cases (53.2%) and resulted in a high proportion of cases that led to payment (40.0%). Other common alleged injuries were facial nerve injury (27.7%), tympanic membrane perforation (23.4%), need for additional surgery (42.6%), and lack of informed consent (31.9%). In addition, cases resulting from acoustic neuroma or stapedectomy resulted in higher payments to the plaintiffs (average 3, 498, 597 and 2, 733, 000, respectively). Conclusions: Malpractice trials were resolved in the defendant's favor in the majority of cases. Cerumen removal was the most common procedure leading to complaint and the procedure most likely to result in payment. Hearing loss was the most common injury cited. Payment was highest in acoustic neuroma and stapedectomy cases.